SUPER-FRUIT: AS A POTENTIAL OPTION TO MITIGATE MALNUTRITION IN INDIAN SUBCONTINENT - Sau, Sayan; Sarkar, Sukamal; Deb, Prahlad; Ghosh, Bikash (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Health and wellness are key drivers of new product development, globally. Obesity and excess calories are issues on one extreme and lack of nutrients is an issue at the other extreme. Consumers are also seeking out new kinds of indulgence, driving demand for new ethnic and exotic flavours and authentic regional products. The health benefits of super-fruits have made them successful as ingredients for food companies and as a source of exciting new flavours for consumers. The super-fruits deemed super by nutrition scientists are packed with antioxidants, fibre, vitamins, minerals and other nutrients that improve health condition. The importance of super-fruits as a necessary part of the human diet and as cash crops is well recognized. They help to prevent a number of extremely chronic human diseases. In recent years this term - originally used by the food industry to indicate fruit having an exceptional nutrient richness and nutritional qualities, including high concentration of phytochemicals - has been increasingly and generically utilized, mainly for marketing purposes. In, India traditional fruits like bael, aonla, pomegranate, guava, pineapple, coconut, grapefruit, litchi, jackfruit, papaya, grape and so many indigenous minor fruits are rich in above mentioned phyto-chemicals & anti- oxidant compound that include them in the list of super fruit. In this present paper we critically review the extraordinary-therapeutic characteristics of Super-fruit, mainly to aware the common people and to speed-up the super-fruit cultivation. Â  Keywords: Super-fruits, Phyto-chemicals, Antioxidant, Malnutrition, Human health